A Comparative Study on Genz Perception About Frozen Food & Homemade Cooked Food on Ahmedabad - Chauhan, Aymanmiya; Saiyad, Nikhat (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
Research is recommended to explore how advanced technology, cultural diversity, and sustainability influenced this generation's eating preferences. In this study, we will observe how the perception of Generation Z toward frozen food versus homemade cooked meals changes. We will also focus on age and how age plays an important role in and influences these preferences. We have made a survey filled out by 141 people, and the researchers analyzed data with a chit-square test to see if age was connected to food choices or not. As seen in the result, there is no significant link between age and preferences for frozen food or beliefs about its convenience and nutrition. But we have also seen that convenience was a key reason people prefer frozen food, and also family tradition and culture have had a greater impact on the choices of home-made cooked food. In fact, we also found out that people are not into cooking; they don’t enjoy cooking as much as expected, suggesting a gap between the idea of cooking as well as fun and the real satisfaction from it.